Strategi Pembuatan Konten Kreatif Brand Ambassador (Analisis Academic Branding Instagram Universitas Telkom) - Rahmaraina, Aliyah; Adim, Adrio Kusmareza (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2024)
Marketing orientation in educational institutions needs to be adjusted to the impact of globalization and innovative marketing strategies used by companies, especially through social media platforms such as Instagram. This research was conducted to analyze creative content creation strategies by Tanjidor (Telutizen Menjadi Ambassador) as Telkom University's brand ambassador in carrying out academic branding via Instagram. This research was carried out using descriptive qualitative methods and based on a case study on Instagram @telkomuniversity. The results of this research conclude that Tanjidor as the brand ambassador of Telkom University has succeeded in implementing creative strategies on Instagram social media by creating content that includes information and messages related to Telkom University in achieving the academic branding goals that have been set